Nitrous Oxide for Intrauterine Device Insertion in Nulliparous Women: A Randomized Controlled Trial [22]. (May 2015) - Singh, Rameet H.; Thaxton, Lauren D.; Carr, Shannon; Leeman, Lawrence Michael; Schneider, Emily; Espey, Eve
Abstract : INTRODUCTION: Intrauterine device (IUD) insertion is a painful procedure, particularly for nulliparous women. Interventions to reduce IUD insertion pain have not been identified. Nitrous oxide administered with oxygen is a safe analgesic with minimal side effects. We compared IUD insertion pain reported by nulliparous women randomized to 50/50 nitrous oxide with oxygen versus oxygen alone. METHODS: This double-blind, randomized controlled trial enrolled nulliparous women ages 13–45 years desiring IUD insertion. Women received 50/50 nitrous oxide with oxygen or oxygen alone through a scented nasal mask during IUD insertion. Baseline, anticipated, and maximum procedural pain scores on a 100-mm visual analog scale were collected. Satisfaction with pain management was reported on a 5-point Likert scale and a 100-mm visual analog scale. A sample of 40 women per arm was required to determine a clinically significant difference in mean visual analog scale pain scores of 15 mm with 80% power and α=0.05. RESULTS: Eighty of 93 eligible women were enrolled and randomized. Mean age of participants was 25.6±5.8 years; 72% were non-Hispanic white and 36% were Hispanic. Mean maximal pain scores at the time of IUD insertion were similar between groups (54±25 mm [nitrous oxide] compared with 55±21 mm [oxygen]; P =.85). Linear regression did not change outcomes. Women in the nitrous oxide group were more likely to be satisfied with their pain management ( P =.04) on the Likert scale but did not have lower visual analog scale scores. CONCLUSION: Nitrous oxide did not reduce IUD insertion pain in nulliparous women; however, satisfaction with pain management was higher in the nitrous oxide group.